A parallel combinatorial algorithm for subtle motifs - Arock, Michael; Reddy, Srinivasulu; Reddy, A V (International journal of bioinformatics research and applications, 2010)
In bioinformatics, motif finding is one of the most common problems. It is to locate recurring patterns in the sequence of nucleotides or amino acids. The main difficulty of the problem is that the patterns are not exact matches owing to biological mutations. It is NP-complete. Within the literature many solutions have been provided for this challenging problem. Nevertheless, they do not address certain subtleties. Among them, one is addressed by Hu (2003). In this paper, we propose a parallel combinatorial algorithm for subtle motif finding on a Shared Memory Multiprocessor model. We suggest a method of implementation for the same.